Assessment of speckle tracking strain predictive value for myocardial fibrosis in subjects with Chagas disease - Macêdo, Carolina Thé (2015)
Hospital São Rafael. Departamento de Cardiologia. Salvador, BA, Brasil / Fundação Oswaldo Cruz. Centro de Pesquisas Gonçalo Moniz. Salvador, BA, Brasil